Beyond Adult Stem Cells: Dedifferentiation as a Unifying Mechanism Underlying Regeneration in Invertebrate Deuterostomes - Ferrario, Cinzia; Sugni, Michela; Somorjai, Ildiko M. L.; Ballarin, Loriano (Frontiers in Cell and Developmental Biology, 2020)
The diversity of regenerative phenomena seen in adult metazoans, as well as their underlying mechanistic bases, are still far from being comprehensively understood. Reviewing both ultrastructural and molecular data, the present work aims to showcase the increasing relevance of invertebrate deuterostomes, i.e. echinoderms, hemichordates, cephalochordates and tunicates, as invaluable models to study cellular aspects of adult regeneration. Our comparative approach suggests a fundamental contribution of local dedifferentiation -rather than mobilisation of resident undifferentiated stem cells- as an important cellular mechanism contributing to regeneration in these groups. Thus, elucidating the cellular origins, recruitment and fate of cells, as well as the molecular signals underpinning tissue regrowth in regeneration-competent deuterostomes, will provide the foundation for future research in tackling the relatively limited regenerative abilities of vertebrates, with clear applications in regenerative medicine.